The electric powered two- wheeled vehicle market in both global and European perspectives - Sławomir Dorocki (Prace Komisji Geografii Przemysłu Polskiego Towarzystwa Geograficznego)
Nowadays, many countries in the world are taking action to reduce carbon dioxide emissions. One of the solutions is to promote energy-efficient and environmentally friendly transport systems of which a specific example is electric vehicles (EV) including cars, motorcycles and mopeds. The article analyses the global development of electric two-wheeled vehicles (ePTW) with China the world leader in the development of ePTW electromobility. China’s high position is due to both economic conditions (domestic raw material base, location of production plants) and top-down state support. Today, it is the financial support of programs promoting the purchase of electric motorcycles and mopeds that is the most important factor in increasing their sales. Electric mopeds have now become the fastest growing means of urban transport in many European countries influenced by electric bicycles being classified as e-mopeds.